Assessment of floristic diversity and documentation of traditional knowledge about the wild medicinal plants of Hercho valley, District Astore, Gilgit-Baltistan, Pakistan - Hussain, Muzahir; Hussain, Imran; Khan, Sher Wali; Abbas, Qamar (Ethnobotany Research and Applications, 2026)
Background: Investigating wild medicinal plants and their traditional uses is essential for understanding local healthcare, especially in remote areas. This study examined the floristic distribution and traditional uses of wild medicinal plants by the inhabitants of Hercho valley in Gilgit-Baltistan (GB), Pakistan. Methods: Ethnobotanical data were collected from 100 local informants through extensive fieldwork. This involved the use of the Global Positioning System, Geographic Information System, and various techniques such as medicinal and aromatic plants (MAPs), Frequency citation, Relative Frequency Citation, Use Value, Informant Consensus Factor, and Fidelity Level, all facilitated by an open-ended questionnaire. Results: In total, 186 plant samples were identified, representing 62 families and 105 species with medicinal applications. Data analysis used statistical indices including Frequency Citation, Relative Frequency Citation, Use Value, Fidelity Level, and Informant Consensus Factor. Relative Frequency Citation measures citation frequency, with Cicerbita decipiens var. multifida having the highest RFC (0.9), followed by Aconitum heterophyllum (0.6) and Lactuca decipiens (0.5). The highest Use Value was recorded for Cicerbita decipiens var. multifida (0.8). The Informant Consensus Factor assessed knowledge sharing among the community, showing strong consensus for gastrointestinal (0.75) and respiratory (0.71) ailments, which received the most citations (gastrointestinal: 180; respiratory: 100). Higher Informant Consensus Factor values indicate prevalent ailments, likely due to poor socioeconomic conditions. Fidelity Level shows the percentage of informants preferring specific plants for ailments; 21 plants achieved high FL values (10-100%), with Aconitum heterophyllum, Viola biflora, and Cicerbita decipiens var. multifida at 100%. Conclusions: These findings highlight the significance of wild medicinal plants in local healthcare practices, particularly during the COVID-19 pandemic. This study underscores the economic value of MAPs and their potential for pharmaceutical development. Keywords: Ethnobotanical survey, Traditional medicine, Therapeutic properties, Geographic information system